Recognition of previous learning: challenges and opportunities for technical and university careers of the area of physical activity, in a model by competences (Revista horizonte, 2021)
At present, where economic and management factors are key and influence educational phenomena, it is necessary to carry out a review of professional training processes within universities. At present, competence-based education tends to focus from the learner, transforming the daily tasks, learning and their results, understanding these learning as the set of competencies that includes knowledge, understanding and skills. The objective of the work is to be able to provide information regarding the changes and challenges of the third millennium, inherent to quality professional training, scientific advances, on which education should focus. Highlighting the situation in Chile and Latin America, with the changes that have occurred in the different curricular reforms at the university level to which the Catholic University of Temuco under a competency-based model is not attached. Understanding that there is a lack of mechanisms for transferring students within and between institutions of the same sector and level of professional training and between institutions of different sectors and levels. The National Qualifications Framework is made explicit and how through initiatives of Innovation to teaching the Catholic University of Temuco promotes evaluative initiatives that help articulate careers in the area of Physical Activity Cs It ends with an evaluative proposal with its theoretical justifications regarding an educational model based on competencies.